Strategi Meningkatkan Kualitas Kinerja Aparat Desa Mekarsari dengan Pendekatan Pengembangan dan Pola Manajemen Sumber Daya Manusia - Otong Sugianto (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
This study aims to find out what strategies are used to improve the performance of the Mekarsari Village apparatus. How to approach the development of human resources for the Mekarsari Village Apparatus. As well as knowing the pattern of human resource management in the Mekarsari Village apparatus. This study uses a qualitative approach with phenomenological methods, data collection techniques using observation, interviews and documentation. Research resource persons from the Village Head, Village Apparatusand the Mekarsari Village community. The analysis technique uses SWOT analysis. The validity test used the source training method and technical triangulation methods. The results of the study show that the strategies implemented to improve the quality of the performance of village officials in Mekarsari are carried out by: 1) Increasing the quality and quantity of employees through continuing to higher education, attending training, technical guidance, courses, seminars, work shops, etc. which aim to increase knowledge and employee experience. 2) Increase the number of employees according to the needs and the ideal number for a village. 3) Improve office facilities and infrastructure. The human resource development approach model in Mekarsari Village includes four approach methods used to develop employees: formal education, assessment, various work experiences, and personal relationships. The Strategy to Improve the Performance Quality of Mekarsari Village Officials with the Development Approach and Human Resource Management Pattern is quite effective in improving the performance quality of the Village apparatus. This can be seen from the quality of service which is more effective and efficient than before.